Personality Types and Leadership Characteristics. A Mini Review - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Stavrogiannopoulos, Anastasios; Tsagri, Angeliki; Tsogka, Danai; Lourida, Konstantina (Technium Business and Management, 2023)
The investigation of the relationship between personality types and leadership characteristics has been a central focus within the realms of organizational and psychological research. Several personality frameworks, such as the Myers-Briggs Type Indicator (MBTI) and the Big Five Personality Traits, have been utilized to gain insight into the impact of inherent personal tendencies on leadership styles. Although certain personality traits, such as extroversion, may tend to influence individuals towards specific leadership styles, it is apparent that effective leadership is not limited to any type. In contrast, it is frequently observed that influential leaders demonstrate a confluence of characteristics, placing particular emphasis on their ability to adapt and maintain situational awareness. This review highlights the significance of comprehending the interaction between individual personality types and the complex requirements of leadership positions.